World Trade: Is It Taking ‘U’ Turn? - Rao, Prof. Pulapa Subba (IJRDO - Journal of Business Management, 2018)
Volume of world trade was just marginal up to 1800s and has grown since 1945. But it  has grown by leaps and bounds due to the second stage of globalization, establishment of World Trade Organisation in 1995, reduction of export and import restrictions particularly tariffs, technological revolution particularly paradigm shifts in information technology during 1990s,  etc. However, there have been indications of ‘U’ turn of volume world trade as well as exports and imports of most of the countries since 2012. This paper presents the trends in exports and imports and explores the reasons for decline in the volume of world trade.